Introduction to solid-state theory - Madelung, O. (Otfried) (Springer series in solid-state sciences, 1996)
This textbook for graduate students of physics and materials science also provides the theoretical background needed by physicists carrying out research in pure solid-state physics and its applications to electrical engineering.